The Influence of Food and Beverage Product Marketing on Consumer Purchase Interest in MSME Actors in Makassar - Rezky Naim; Sultan; ST. Rukaiyah; Rahmat Laan (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2023)
The purpose of this study was to examine the effect of food and beverage variables on purchasing preferences. Data collection was carried out by distributing questionnaires to MSME stakeholders in five sub-districtsspread across the city of Makassar. Hypothesis testing here involves the use of multiple regression analysis. The results of this study show that food and beverage variables have a strong effect on purchase intent.Background: Buying interest in consumers is a very important phenomenon in marketing activities. Buying interest is consumer behavior that bases the purchase decision to be made". From the above opinion, it can be said that the buying interest arises from within a consumer after consuming and feeling repository.unimus.ac.id 4 own benefits received when consuming a product. Consumer buying interest can be influenced by product quality. Some of the descriptions above, the author is interested in knowing the relationship between Product Quality and Buying Interest, so the researcher conducted a study entitled Based on the description above, the purpose of this study is to test whether the product has an effect on consumer interest in shopping for MSME Actors.Method: The respondents here are MSMEs in Makassar City. This research method uses purposeful sampling method. The duration of this study was carried out for 3 months due to the time of distribution of questionnaires and the coverage covered by all MSME actors in the city of Makassar. For the evaluation of each statement item using a 5-point Likert scale, where 1 strongly disagrees and 5 strongly agrees. Hypothesis testing is performed using simple linear regression analysis. The formulaof the regression equation is: Y = a +b1X1+eResult: The product has a positive effect on the desire to buy. This can be seen from the significance value smaller than alpha 0.000 (<0.05)which indicates a significant influence. A positive beta value of 0.464means that the influence of the product on customer decisions is positive.That is, the better and more diverse products offered by MSME agents,the more people are interested in making purchases. This can be seenfrom the significance value below alpha 0.000 (<0.05) which indicates the effect of having a positive beta value of 0.345. This means that the effect of price on purchase intention is positive. Conclusion: From the results of research and discussion, several things can be concluded. First, the variety and quality of products offered by small and medium-sized businesses arouses interest and desire to buy from customers andpotential consumers. Second, attractive prices also encourage consumers to buy bamboo products from MSME players.